Analysis of the Effect of Final PPh Collection on the Transfer of Land and/or Building Rights to the Financial Aspects of PT. Indonusa Property Center Medan - Siregar, Melinda (International Journal for Educational and Vocational Studies, 2020)
This study aims to determine how the results of the analysis of the application of Final Income Tax at PT Sentra Properti Indonesia and its influence on the profit and loss results of PT Sentra Properti Indonusa Medan. Of the problems found, namely the application of Final Income Tax on the transfer of rights to land and or buildings at PT SPIM regarding payment of income tax on the transfer of rights to land and / or buildings and see the profit and loss. From the results of the analysis it was found that by comparing the final PPh tariff using Article 17 tariff, it turns out that using the Final PPh tariff is more efficient than using Article 17 tariff. It can be seen that the tax paid if using Final PPh is Rp. 1,235,520,000 while the tariff used in Article 17 the amount of tax to be paid is IDR 2,276,599,343 greater than using the Final Income Tax rate so PT. Indonusa Property Centers are more efficient at using Final PPh rates than using Article 17 tariffs. It can be concluded that using Final PPh Tariffs is more efficient than using Article 17 and the application of Profit and Loss to PTs does not significantly influence.